Would Neonatal Healthcare Professionals Disclose Personal Opinions When Counseling Parents About Value-laden Decisions? - Arnold, Christine; Eychmüller, Julian; Hediger, Dina; Baumann, Lukas; Jaisli, Sophie; Kidszun, André (Klinische Pädiatrie, 2024)
Background To explore the attitudes of neonatal healthcare professionals towards disclosing personal opinions when counseling parents about value-laden decisions using scripted video animations, with a view to comparing these later with the attitudes of parents of preterm infants.Methods An exploratory study was conducted during the 5th Annual Meeting of the Joint European Neonatal Societies in Rome. Data were collected via a web-based survey during a live session. Two scripted video animations were presented and discussed, one with and one without disclosure of the physician’s personal opinion.Results Sixty-nine healthcare professionals from 19 countries were enrolled. Forty-seven (68.1%) respondents stated that disclosing personal opinions would “unduly influence” the parents' decision-making process. Thirty-seven (53.6%) participants would not have given their personal opinion in the case presented, and 45 (65.2%) participants stated that disclosure of the physician's personal opinion would result in parents being less prepared for decision-making. Discussions were dominated by underlying values and culture rather than the process of sharing opinions.Discussion and Conclusions The study provides new insights into the opinions of healthcare professionals on the disclosure of personal opinions when making difficult treatment decisions, but further research may require a more nuanced approach in different scenarios. Further research with a larger sample and different scenarios is needed to explore in more depth healthcare professionals’ and parents’ attitudes of autonomous decision-making.
Keywords: disclosing personal opinions; value-laden decisions; parents; healthcare professionals; scripted video animation